Quantification of phenolic compounds in selected herbs using HPLC - Mohd Yusof, Nor Amaliana Syazwani; Abdullah Thaidi, Nur Imanina; Haron, Normah; Mat Jusoh, Hanapi; Muhamad Bunnori, Noraslinda (2018)
The present study was conducted to profile the presence of selected individual phenolic compounds samples namely Citrus hystrix, Coriandrum sativum, Murayya koenigii, Polygonum minus, Ocimum basilicum and Anacardium occidentale) in three different fractions (free, soluble bound and insoluble bound) using optimized HPLC conditions with C6-Phenyl column. The concentrations of each compound were quantified by the calibration curves with R2=0.999. The results showed that caffeic acid, sinapinic acid, p-coumaric acid and gallic acid were the common phenolic acids found in all fractions. Caffeic acid was the main compound extracted from the free phenolic fraction of C. hystrix (87.34 ± 103.94 µg/g of extract), while sinapinic acid was found in the highest concentration in soluble and insoluble bounds (117.69 ± 10.19 and 25.89 ± 1.29 µg/g of extract), respectively. In C. sativum, the highest concentration of caffeic acid was seen in the insoluble bound extract (461.41 ± 94.66 µg/g of extract) (p< 0.05). For M. koenigii, sinapinic acid was the major compound detected in free phenolic extract and insoluble bound extract (271.17 ± 22.74 and 106.57 ± 5.79 µg/g of extract), respectively. Gallic acid was predominated in the soluble bound of P. minus extract (391.83 ± 37.43 µg/g of extract) with p<0.05. Highest concentrations of caffeic acid were found in all fractions of O. basilicum extract (soluble bound, insoluble bound and free phenolic: 442.60 ± 10.78, 342.21 ± 63.30 and 18.99 ± 0.42 µg/g of extract, respectively) with p<0.05. In conclusion, the hydroxycinnamic acid is dominated in the plant as compared to hydroxybenzoic acids.